PROBLEMATIKA PEMBELAJARAN PAI PADA MADRASAH TSNAWIYAH DI WILAYAH BARAT SELATAN ACEH - syibran Mulasi (Islam Futura, 2019)
This study aims to see the problems faced by teachers in Islamic Education learning (PAI) and the factors that cause these problems to occur. Data collection was focused on islamic junior hight school in five districts in the South West of Aceh, namely Aceh Jaya, Aceh Barat, Nagan Raya, Aceh Barat Daya and Aceh Selatan. This study uses a qualitative approach. Data collection techniques were carried out by interviewing and observing Islamic education teachers and the principle. the result showed that the problem of islamic eucation learning occurs because of the lack of facilities and infrastructure of learning, such as reading books and other supporting learning facilities in which it affects the lack of interest in reading and student learning at school. While the factors that led to these problems were limited variations in methods and models of teaching in learning esed by the teachers. furthermore, Student learning motivation is not so increased and learning is more dominant in cognitive nature, so that students understand about religion only but have not been able to maximize it in daily life. In addition, the solution given by Islamic education teachers motivate and advice the students to get better learning. then, teachers develops learning media for education by utilizing all available facilities so that the enthusiasm of students' learning in the teaching and learning process are able to increase.